Gambaran Epidemiologi Infeksi Oportunistik Tuberkulosis Pada Penderita HIV di Puskesmas Percontohan HIV/AIDS Kota Makassar Tahun 2015 - Megawati, Megawati; Azriful, Azriful; Damayati, Dwi Santy (HIGIENE: Jurnal Kesehatan Lingkungan, 2016)
Tuberculosis (TB) is a disease of opportunistic infections most often found in patients with HIV / AIDS. This study aims to describe the epidemiology of tuberculosis Opportunistic Infections In HIV patients at the health center in Makassar pilot HIV 2015. This type of research is quantitative descriptive research design. The population in this research that all patients with HIV / AIDS were diagnosed with tuberculosis infection in specimen community health centers HIV / AIDS in the city of Makassar as many as 14 people with sampling techniques using total sampling. The results showed that the characteristics of HIV patients with tuberculosis infection based on gender most affected are males by 11 (78.6%) of respondents, by age most affected is the 26-45 year 8 (57.1%) of people, based education at most that low educated as much as 8 (57.1%) of people, based on the work that people who work as many as eight (57.1%) of people, based on revenue at most that low-income by 8 (57.1%) of people, by the time diagnosis is categorized in a long time that as many as 14 (100%) of people, based on the history of contact at most that the patient had no history of contact as many as 11 (78.6%) of people, based on the density of dwelling at most that do not qualify as much as 9 ( 35.7%) of people, based on home lighting most that do not qualify as many as 11 (78.6%) of people, and based on home ventilation most that do not qualify as many as 10 (71.4%) persons. Keywords : opportunistic infections, tuberculosis, HIV